Retention in care among clinically stable antiretroviral therapy patients following a six‐monthly clinical consultation schedule: findings from a cohort study in rural Malawi. Issue 11 (18th November 2018) - Wringe, Alison; Cawley, Caoimhe; Szumilin, Elisabeth; Salumu, Leon; Amoros Quiles, Isabel; Pasquier, Estelle; Masiku, Charles; Nicholas, Sarala
Abstract: Introduction: Longer intervals between clinic consultations for clinically stable antiretroviral therapy (ART) patients may improve retention in care and reduce facility workload. We assessed long‐term retention among clinically stable ART patients attending six‐monthly clinical consultations (SMCC) with three‐monthly fast‐track drug refills, and estimated the number of consultations "saved" by this model of ART delivery in rural Malawi. Methods: Stable patients (aged ≥18 years, on first‐line ART ≥12 months, CD4 count ≥300 cells/mL 3, without opportunistic infections, not pregnant/breastfeeding) were eligible for SMCC, with three‐monthly drug refills from community health workers. Early enrollees were those starting SMCC within six months of eligibility, while late enrollees started at least 6 months after first eligibility. Kaplan–Meier methods were used to calculate cumulative probabilities of retention, stratified by timing of their enrolment and from first six‐monthly clinical consultation. Cox regression was used to measure attrition hazards from the first six‐monthly clinical consultation and risk factors for attrition, accounting for the time‐varying nature of their eligibility and enrolment in this model of care. Results: From 2008 to 2015, 22, 633 clinically stable patients from 11 facilities were eligible for SMCC for at least three months, contributing 74, 264 person‐years of observation, and 18, 363 persons (81%) initiated this model of care. The median time from eligibility to enrolment was 12 months and the median cumulative time on SMCC was 14.5 months. Five years after first SMCC eligibility, cumulative probabilities of retention were 85.5% (95% CI: 84.0% to 86.9%) among early enrollees and 93% (95% CI: 92.8% to 94.0%) among late enrollees. The cumulative probability of retention from first SMCC was 97.0% (95% CI: 96.7% to 97.3%) and 86% (95% CI: 85% to 87%) at one and five years respectively. Among eligible patients initiating SMCC, the adjusted hazards of attrition were 2.4 (95% CI: 2.0 to 2.8) times higher during periods of SMCC discontinuation compared to periods on SMCC. Male sex, younger age, more recent SMCC eligibility and WHO Stage 3/4 conditions in the past year were also independently associated with attrition from SMCC. Approximately 26, 000 consultations were "saved" during 2014. Conclusion: After five years, retention among patients attending SMCC was high, especially among women and older patients, and its scale‐up could facilitate universal access to ART.